If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (72x + -47y) + -1(63x + 21y) = 0 Remove parenthesis around (72x + -47y) 72x + -47y + -1(63x + 21y) = 0 72x + -47y + (63x * -1 + 21y * -1) = 0 72x + -47y + (-63x + -21y) = 0 Reorder the terms: 72x + -63x + -47y + -21y = 0 Combine like terms: 72x + -63x = 9x 9x + -47y + -21y = 0 Combine like terms: -47y + -21y = -68y 9x + -68y = 0 Solving 9x + -68y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '68y' to each side of the equation. 9x + -68y + 68y = 0 + 68y Combine like terms: -68y + 68y = 0 9x + 0 = 0 + 68y 9x = 0 + 68y Remove the zero: 9x = 68y Divide each side by '9'. x = 7.555555556y Simplifying x = 7.555555556y
| (49x+62y)-(21x-23y)= | | z/3-3=5 | | v-3/5=8.5 | | 1/5a=3.1 | | n/5+11=13 | | (12z^6-32z^6)/4z^2 | | C=400+15n | | (64x+56y)-(7x+38y)= | | 4(4x+14)+9x-17= | | X+7x/4=33 | | (9+3x)-3x= | | 3x-5(x+4)=-(x-7) | | 9(x-7)+14(x+10)= | | 4(2x+12)-6x= | | 7(6x+4)+5x= | | 7(t-3)+7t=7(2t+5)-12 | | 5(2x+6)-20= | | 2x^2-32x-72=0 | | (6x+16)-6= | | (55x+60y)-(10x-22y)= | | 7(5x+12)+13x-12= | | (63x+47y)-(3x-6y)= | | 1.6q-2.5-1.5q=-0.9q-3.3 | | =(-7)*10+5*10 | | (2x-x+9x^2)/(-1+3x) | | (w^2+10w+25)(w-2)=a+70 | | -8y+4=-9y+1 | | 2(x-5)+7=17 | | 35=x^2+x | | =444444+5362664536 | | (w^2+10w+25)(w-2)=70 | | 3x-24y=-30 |